Urgensi Kepemimpinan Transformatif Bagi Perpustakaan Perguruan Tinggi - Sari, Kristina (STAIN Ponorogo, 2015)
TheÂ globalizationÂ eraÂ hasÂ givenÂ aÂ consequenceÂ of massive changesÂ inÂ peopleâsÂ lifeÂ includingÂ theÂ universityÂ organization.Â The increasing of information technology and the rapid fow of information makeÂ theÂ universityÂ libraryÂ asÂ anÂ informationÂ centerÂ andÂ knowledge undergoesÂ variousÂ changesÂ inÂ theÂ roleÂ andÂ functions.Â AtÂ such circumstances, the role of the leadership of the university library should have a clear vision for the challenges that occur. The quality of a leader in the process of ongoing changes should have a future-oriented. Libraries as a nonproft organization cannot avoid the changes, the presence of the development of information technology is a major external impact will changeÂ theÂ elementsÂ ofÂ theÂ organizationâsÂ library. EachÂ organization hasÂ diferentÂ targetsÂ to meetÂ theÂ needsÂ andÂ theÂ dominantÂ factorÂ that encourage the changes.